Paklouby pánve - Taller, S; Srám, J; Lukás, R; Krivohlávek, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2009)
PURPOSE OF THE STUDY Surgery for the nonunion or malunion of pelvic fractures is not common even at specialised departments. This article presents the authors experience with this procedure, completed with case studies and a review of relevant literature. MATERIAL AND METHODS From 1998 to 2007, a total of 359 patients underwent surgery for pelvic trauma. In the same period, eight surgeries on nonunions or malunions of the pelvis were performed, three in men and five in women. The average age of the patients was 37.3 years (range from 15 to 68). The primary treatment included conservative therapy (two patients), external fixation (three patients) and osteosynthesis of the anterior pelvic segment in another three patients. Reconstructive surgeries were always executed for nonunion or malunion or for both conditions together. Patients suffered most often from pain, limping, from the need of using crutches or leg shortening; no diffuculties occurred while sitting. Surgery for nonunion or malunion was performed at the average period of 29.3 months (range from 6 to 84) after injury. Surgical techniques and risks are described in detail. RESULTS Two patients suffer from persistent pain after surgery. In one patient, it is due to partial sacroiliac ankylosis with pathological mobility of the remaining part of the sacroiliac joint together with nonunion of the fractured dorsal part of the ilium. In the other one, pain comes from muscular dysbalance, as well as from chronic lesions in the sacroiliac joint and from scoliosis, despite the fact that the pelvis was successfully reconstructed 7 years after the initial injury. Four patients have no or only transient pain. In four patients limping disappeared after surgery; in two it is still persisting. One of these is the patient with partial sacroiliac joint ankylosis, while symphysis pubic diasthesis persists in the other. Leg length difference, sitting problems or other complaints following surgery are not observed. Four patients developed union detected radiologically, widening of the symphysis persists in one patient and sacroiliac joint problem in another one. Excellent results with anatomic integrity in all three x-ray projections were achieved in only two patients. Satisfactory outcome with a residual deformity of less than 1 cm of the vertical or posterior displacement or up to 15-degree rotation in any plane was achieved in three patients. A poor outcome involving more than 1-cm dislocation was found in one case. DISCUSION The most common cause of poorly healed pelvic fractures is a misdiagnosis of the primary injury and a subsequent conservative way of treatment. Injuries to the posterior pelvic segment are repeatedly underestimated. A frequent error in pelvic ring fracture therapy is that only the anterior pelvic segment is treated surgically, often with only a simple external fixator inserted in the iliac crests. In addition, the treatment strategy is often decided on in hospitals whose surgeons have not enough in pelvic trauma surgery. The most frequent complaints associated with an inadequate treatment are pain, walking problems and limping. Sitting can be difficult in some patients. Urinary bladder can be compressed with the result of frequent and urgent miction, and vaginal compression could bring about dyspareunia. Additionally, pelvic deformations in women can aggravate delivery. Cosmetic changes due to a prominent sacrum, a prominent greater trochanter or distal spine scoliosis are also of concern. The method of an accurate measurement of anatomic alterations of the pelvis is presented. CONCLUSIONS Early surgery of the pelvic trauma enables an adequate restoration of pelvic anatomy and provides conditions for good and reliable stability of both the posterior and anterior pelvic segments. Late repairs of nonunions or malunions are demanding and associated with a high risk of serious complications, often with long-term sequelae. Key words: pelvic fracture, malunion, nonunion.
Keywords: Fractures, Malunited; Humans; pánevní kosti; Radiography; lidé středního věku; Fractures, Ununited; radiografie; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; Young Adult; špatně zhojené fraktury; Pelvic Bones; mužské pohlaví; nezhojené fraktury; mladiství